Pengaruh Faktor Sikap, Norma Subjektif, Demografi, Sosioekonomi serta Literasi Keuangan Syariah dan Konvensional terhadap Minat Berwirausaha pada Mahasiswa - Fajar Adi; Ujang Sumarwan; Idqan Fahmi (Department of Islamic Economics, IPB University, 2017)
This cross sectional study aimed to analyse influence of attitude, subjective norm, demography, sosioeconomic and shariah and conventional financial literacy toward entrepreneurship intention among college students. Refers to the model of Theory of Reasoned Action developed by Fishbein dan Ajzen, behavioral intentions are a function of attitude toward behavior and the subjective norm (Sumarwan 2011). Respondents were 100 college students selected by convenience sampling methods. Data collection was purposively conducted at public universities located in Jakarta, Bogor, Depok and Tangerang on February 2016 until August 2016. Interview was conducted using reliable and valid questionnaire as a tool. Descriptive analysis on attitude toward entrepreneurship showed that respondents strongly agreed with the attitude statement and subjective norm indicates that they disagree with recommendation from nearest person to start a business. In addition, analysis of the entrepreneurship intention showed that respondents have an interest to become entrepreneur. Regression analysis with dummy variable showed that entrepreneurship intention was significantly affected by variables of attitude toward entrepreneurship and conventional financial literacy (p value <0.05), gender (women tend to be more interested in entrepreneurship as compared to men), experience of taking entrepreneurship class and experience of being entrepreneur (p value <0.10). To increase student’s entrepreneurship intention, it needs efforts from various parties, especially from academics to build attitude toward entrepreneurship and to increase financial literacy among students.